MENINGKATKAN KETERAMPILAN METAKOGNISI DAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MODEL SELF REGULATED LEARNING (SRL) PADA MATERI HIDROLISIS GARAM - Sri Hidayati; Syahmani Syahmani (Universitas Lambung Mangkurat, 2016)
Abstract. Has done research on Metacognition skills using the model of the Self Regulated Learning (SRL) in material hydrolysis of salt in class XI MS 7 SMA Negeri 2 Banjarmasin academic year 2015/2016. This research aims to (1) find out the teacher's activity; (2) increasing the activity of students; (3) enhance the skills of the student's Metacognition; (4) improve cognitive aspects of learning results, affective and psychomotor students; and (5) know the response of students towards learning using Self Regulated Learning model (SRL). The research of using class action research design (PTK) is done in two cycles with a total of six times. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subject is a student of Class XI MS 7 SMA Negeri 2 Banjarmasin with total number of 33 people. Research instrument in the form of instruments Metacognition skills tests and the results of student learning, and instrument in non test in the form of sheets of observation and question form. Data were analyzed with descriptive quantitative analysis techniques and qualitative analysis. The results showed that (1) the activity of the teachers increased from an average overall rating of 44.5 on cycle I became 55 on cycle II; (2) the activities of students increased from an average overall rating of 34.5 on cycle I became 47.5 cycle II; (3) the student's Metacognition skills increased from the average overall rating of rat 48.62 on cycle I became 81.81 on cycle II; (4) the cognitive students increased from 54.54% in cycle I became 90.90% in cycle II, affective students increased from an average overall rating of 8.6 on cycle I became 12.85 cycle II and psychomotor students increased from an average overall rating of 68.25 on cycle I became 85.83 on cycle II; and (5) student response shows excellent categories.Keywords: Metacognition Skills, Self Regulated Learning, Hydrolysis of Salts